Abdominal lymph node metastasis in non-surgical esophageal squamous cell carcinoma: prognostic significance and a novel staging strategy - Zhao, Zongxing; Wang, Hongmin; Liu, Yajing; Li, Minghuan; Li, Mingjun (Frontiers in Oncology, 2023)
Purpose This study aimed to evaluate the feasibility of a combination of abdominal lymph node (LN) metastasis and the number of LNs in esophageal squamous cell carcinoma (ESCC) patients to optimize its clinical nodal staging. Methods A retrospective study, including a total of 707 ESCC patients treated with definitive radiotherapy, was conducted at two participating institutes. Different combinations of LN variables, including abdominal LN metastasis(R1: no-abdominal LNs metastasis; R2: abdominal LNs metastasis), were further analyzed to propose a potential revised nodal (rN) staging. Results The multivariate analyses showed that the number of metastatic LNs and abdominal LNs metastasis were independent prognostic factors for the overall survival (OS). The results showed no significant differences in the OS between the N2 patients with abdominal LN metastasis and N3 patients. The OS of the stage III patients with abdominal LNs metastasis was not significantly different from those with stage Ⅳa. The N3R1 and N1-2R2 had similar hazard ratios (HRs). The N1R1 subset was defined as rN1, the N2R1 subset was defined as rN2, and the N3R1-2 and N1-2R2 subsets were defined as rN3. The HRs of OS of the rN2 and rN3 groups increased orderly. The rN stage could identify the differences in the OS times of each subgroup based on the 8th AJCC cN staging or 11th JES N staging. Conclusions The rN staging, including the number of metastatic LNs and abdominal LN metastasis, might serve as a potential prognostic predictor for non-surgical patients with ESCC.